Before the sky falls again: does the latinofuturista theater imagine other futures? (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This paper brings together a series of reflections and fabrications that inquire into the imaginaries of the future that surround our present, such as the "cancellation of the future," the Anthropocene, and counterfuturism movements, placing them in dialogue with contemporary Latin American artistic and theatrical practices. It also articulates possible Latin American temporalities from a combination of theories that include the ch'ixi thinking elaborated by Silvia Rivera Cusicanqui, and the Amerindian perspectivisms (Eduardo Viveiros de Castro, Déborah Danowski, Davi Kopenawa). Finally, presents a speculative exercise from the idea of Latinfuturismo and briefly analyzes some contemporary  theatrical practices under this framework.
Keywords: Contemporary dramaturgy; Latin America; Anthropocene; Future; Latinfuturism